Intergenerational transmission of human capital in Europe: Evidence from SHARE - Luca Stella (IZA Journal of European Labor Studies, 2013)
This paper extends the previous literature on the intergenerational transmission of human capital by exploiting variation in compulsory schooling reforms across nine European countries over the period 1920-1956. My empirical strategy follows an instrumental variable (IV) approach, instrumenting parental education with years of compulsory schooling. I find some evidence of a causal relationship between parents' and children's education. The magnitude of the estimated effect is large: an additional year of parental education raises the child's education by 0.44 of a year. I also find that maternal schooling is more important than paternal schooling for the academic performance of their offspring. The results are robust to several specification checks.
Keywords: I20; J62; 330; Intergenerational transmission; Human capital; SHARE